Annual Plan 2006-2007 Volume II Uttar Pradesh - Planning Commission (Planning Commission, 2005)
Major Head of Development Rural Development Minor Head of Development Special Programmes For Rural Development Minor Head of Development Rural Employment Minor Head of Development Land Reforms Minor Head of Development Other Rural Development Programmes Major Head of Development Irrigation And Flood Control Minor Head of Development Major And Medium Irrigation Minor Head of Development Minor Irrigation Minor Head of Development Command Area Development Programme7
Government of Uttar Pradesh State Planning Commission